Fish and fishing during the late Islamic period at Rubayqa, northern Qatar: preliminary results (poster) - Russ, Hannah; Petersen, Andrew (Proceedings of the Seminar for Arabian Studies, 2013)
Both the remains of fishing gear and the skeletal remains of fish were recovered from the late Islamic period site at Rubayqa, northern Qatar, during excavations by the University of Wales in 2010. While artefactual and structural evidence for fishing are present at the site, the results of the analysis of skeletal remains of fish are presented here. Fish bones constituted 22% (NISP [number of identified specimens]) of the overall animal bone assemblage from Rubayqa, which was dominated by the remains of domestic mammals, but also included wild mammals, domestic and wild birds, and marine reptiles. The fish remains represented fifteen families of fish, all of which can be found in the Arabian Gulf today. Sea breams (Sparidae) and emperors (Lethrinidae) were the most frequently identified families of fish, closely followed by needlefish (Belonidae), groupers (Serranidae), and sea catfish (Ariidae). The presence of cut marks, burning, and gnawing on the fish remains provides a taphonomic history for the assemblage, allowing an interpretation of fish-processing methods and cooking methods as well as site conditions in the past.